Agricultural R&D in Brazil: policy, investments, and institutional profile - Beintema, Nienke M.; Avila, Antonio Flavio Diaz; Pardey, Philip G. (International Food Policy Research Institute, 2001)
In 1996, Brazil employed more than 5,000 full-time equivalent researchers and spent more than $1 billion (1993 international dollars) on agricultural R&D; about one half of the total agricultural research spending throughout Latin America in that year.